Edukasi Pemanfaatan Tanaman Sebagai Pengusir Nyamuk Untuk Mencegah DBD Pada Warga Kelurahan Kedungwuni Barat Kec. Kedungwuni Kabupaten Pekalongan - Suparyati Suparyati; Abdul Ghofur (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Aedes aegypti is the main vector of dengue hemorrhagic fever. Every year it is estimated that 390-400 million dengue infections occur throughout the world, and 270 million of them occur in Asia, including Indonesia. In Indonesia, dengue cases have spread to all provinces. Based on data from the Ministry of Health, in 2022, the number of dengue cases will reach 131,265 cases. The number of dengue fever deaths reached 1,135 cases with 73% occurring in children aged 0-14 years. So far, dengue fever has been prevented using a fogging program with chemicals and supported by the community who also use chemical mosquito repellents. However, using chemical mosquito repellents is very dangerous for human health. This education aims to provide knowledge to the public regarding how to prevent dengue fever by using plants as an alternative mosquito repellent and as a means of preventing dengue fever. The methods used in this education are lectures and assessing knowledge regarding dengue fever and mosquito repellent plants using questionnaires. The results of the education show an increase in public knowledge regarding dengue fever and mosquito-repellent plants with a mean score of 60 to 85. In conclusion, there is a need for education regarding the prevention of dengue fever and the use of mosquito-repellent plants around us.